Microaggressions against Asian international students in therapy. - Kim, Eunha; Hogge, Ingrid (Professional Psychology: Research and Practice, 2021)
We examined microaggressions toward Asian international student clients in therapy. Participants were nine university counseling center therapists who had themselves been Asian international students with experience in therapy. Data were collected through semistructured interviews and analyzed using interpretive phenomenology. We identified 3 themes (environmental microaggressions, stereotypical assumptions and conceptualizations of Asian international student clients, and culturally insensitive treatment planning or interventions) and 14 subthemes. Subthemes that uniquely emerged in this study included the following: Limited self-disclosure and expression of emotion, outdated views of Asian cultural values and practices, overemphasis on adjustment issues, and condescending and overprotecting the client. Implications for research, advocacy, and practice are discussed. (PsycInfo Database Record (c) 2021 APA, all rights reserved)
Keywords: Asian international students; microaggressions; therapy